2013
DOI: 10.1254/jphs.13033sc
|View full text |Cite
|
Sign up to set email alerts
|

Specific Enhancement of Vascular Endothelial Growth Factor (VEGF) Production in Ischemic Region by Alprostadil — Potential Therapeutic Application in Pharmaceutical Regenerative Medicine

Abstract: Abstract. Alprostadil (lipo-PGE1) is a drug delivery system preparation. This preparation is applied to treat refractory skin ulcers and arteriosclerosis obliterans. We investigated the effects of alprostadil by using the earflap ischemic model. The following results were obtained: 1) Treatment with alprostadil significantly increased the VEGF contents in an ischemic ear; 2) Treatment with alprostadil resulted in strongly expressed VEGF levels only in the ischemic region; 3) Image analysis revealed a significa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
7
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 11 publications
0
7
0
Order By: Relevance
“…When an endothelial cell is damaged following hypoxic conditions, an MR contrast agent can extravagate, leading to the accumulation of contrast agent in the tumor tissue that causes abnormal enhancement. Thus, neovascular permeability is associated with the enhancement degree of gliomas [ 10 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…When an endothelial cell is damaged following hypoxic conditions, an MR contrast agent can extravagate, leading to the accumulation of contrast agent in the tumor tissue that causes abnormal enhancement. Thus, neovascular permeability is associated with the enhancement degree of gliomas [ 10 ].…”
Section: Discussionmentioning
confidence: 99%
“…Vascular endothelial growth factor (VEGF) is a well-known tumor-related biomarker that regulates pathological angiogenesis [ 9 ]. In vivo, VEGF expression promotes angiogenesis and the permeabilization of blood vessels, which is associated with the degree of enhancement in gliomas [ 10 ]. VEGF can also serve as an independent indicator for the prognosis of patients with liver cancer [ 11 ], breast cancer [ 12 , 13 ] and gastric cancer [ 14 , 15 ].…”
Section: Introductionmentioning
confidence: 99%
“…For example, PGE 1 is reported to be effective for treating patients with severe hepatitis and primary graft non-function after liver transplantation (Andrade Jr, Andrade & Santos, 2009). Moreover, it is reported that PGE 1 is a potent stimulator of angiogenesis via upregulation of VEGF expression (Haider et al, 2005; Inoue et al, 2013; Mehrabi et al, 2003). However, the molecular mechanisms behind the phenomena are as yet largely unknown.…”
Section: Introductionmentioning
confidence: 99%
“…Prostaglandin E1 is known to mediate vasodilation and improve microcirculation perfusion. 11,12 Recently, PGE1 has been reported to stimulate fibroblast proliferation. 13 Vitamin C is also well-known for promoting fibroblast production.…”
mentioning
confidence: 99%